Planejamento estratégico de marketing digital em loja de pequeno porte do setor óptico - Costa, Brenda Kynsenng Barbosa da Silva (Brasil, 2024)
The aim of this study is to draw up a strategic digital marketing plan for a small optical shop, with the aim of optimizing its online presence and increasing its visibility in the digital environment. To this end, an action research approach was adopted, combining qualitative methodologies, such as participant observation, and quantitative methodologies, such as questionnaires with consumers. The application of tools such as SWOT analysis and the 8P's methodology are demonstrated, offering a practical model for developing and implementing digital marketing strategies in micro-enterprises. The results highlight the viability and effectiveness of these tools for small businesses, demonstrating their ability to align theory and practice in the formulation of personalized, data-driven strategies. And it provides a relevant model for managers and researchers interested in integrating strategic and operational practices in resource-limited contexts such as micro and small businesses.